PLANTING MACHINE WORKING SECTION AND PARAMETERS FOUNDATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the theoretical research results on the structure, operation and the machine working section some technological parameters for transplanting vegetable seedlings.